KONSELING ISLAMI DALAM MENGEMBANGKAN KEPRIBADIAN SISWA MAN NGAWI - Samsudin Samsudin; Muh. Rodhi Zamzami (STAI Ma'had Aly Al-Hikam Malang, 2019)
At each individual very clearly has a cirikhas settled in a person in different situations and in different conditions, capable of distinguishing between one individual with another individual. And the personality types, there are individuals who are friends, fun, friendly, talkative, impulsive and so forth. Guidance and counseling should help facilitate students to develop all aspects of his personality as optimally as possible, so that the students realized the formidable face of the present and the future. Guidance and counseling services are an integral part of the overall educational process at school. The problems in this research are: (1) How does the personality of students MAN Ngawi ?. (2) How does the counseling teachers in developing students' personalities MAN Ngawi ?. (3) What is the impact of counseling on the development of personality of students MAN Ngawi?This research was conducted in MAN Ngawi uses qualitative research with case study approach. Techniques of collecting data using interviews, observation and documentation. For the data analysis techniques using groove Miles and Huberman that include: data collection, data reduction, data presentation and conclusion.Conclusion to answer the problem of this study were (1) Personality existing student-MAN Ngawi still unstable, it is evident reasonableness of delinquency alone, yet has the responsibility, the lack of independence and lack of discipline, student MAN Ngawi who often break the rules like not wearing attributes, late entry into school, crowded in the classroom, playing phone while tutoring, fight among their peers and lack of respect for teachers. (2) Teachers counseling to develop the personality of students MAN Ngawi by conducting counseling individuals and groups, held a home visit if one does not enter without permission of its conditional, gave a warning with a call parents when absent from school one without permission and mendatangkangkan parents to the school if up to two times absent from school without permission and give points to students who commit violations against pollutes school. (3) The impact of counseling on the development of personality of students MAN Ngawi is the perubabahan on students from less discipline is discipline, the emergence of a high sense of responsibility and begin to infuse honest.